Lectotypification of 4 names of Viburnum (Adoxaceae) - Zhao, Liao-Cheng; Tang, Ming (Phytotaxa, 2023)
Examination of the protologues of Viburnum henryi, V. brachybotryum var. tengyuehense, V. theiferum and V. ternatum revealed that at least two gatherings were mentioned as types for every one of them, making it necessary to designate a lectotype for each of the 4 names.